Physiochemical Properties of Pyrolysis Oil Derived from Fast Pyrolysis of Wet and Dried Rice Husk in a Free Fall Reactor - Naqvi, Salman Raza (2014)
Rice husk is considered as a massive agricultural lignocellulosic biomass residue for the production of bio-based fuels and chemicals products. The purpose of this study is to investigate the physiochemical properties of the pyrolysis-oil derived from wet and dried rice husk fast pyrolysis process. The experiments were performed in a drop type fixed-bed pyrolyzer at the pyrolysis temperature of 350 to 600 °C. The products, char, pyrolysis-oil and gas, yield are investigated. The pyrolysis-oil derived from dried rice husk contained higher Carbon and Hydrogen and less oxygen contents than the pyrolysis-oil obtained from wet rice husk. FT-IR results showed the oxygenated compounds present in both pyrolysis-oil. The pyrolysis oil from dried rice husk has higher concentration of hydrocarbons as compared to wet rice husk pyrolysis-oil. The dried rice husk pyrolysis-oil produced more phenols and less carboxylic acid as compared to wet rice husk pyrolysis-oil at 500 °C. More volatile released in dried rice husk conversion produced more volatile compounds. These findings suggest that the original moisture present in biomass samples is the major influencing parameter on the thermal degradation of biomass during fast pyrolysis process.